Effective noninvasive body contouring by using a combination of cryolipolysis, injection lipolysis, and shock waves - Faulhaber, Jörg; Sandhofer, Matthias; Weiß, Christel; Sattler, Gerhard; Sadick, Neil S. (Journal of cosmetic dermatology, 2019)
Background Cryolipolysis combined with shockwave therapy has been previously shown to have synergistic effects in body contouring results. Objective This open-label, prospective, multicenter, comparative study investigated the safety and efficacy of combined cryolipolysis, shockwave therapy with cryolipolysis, shockwave therapy, and injection polyenylphosphatidylcholine-based lipolysis. Methods Enrolled patients were treated in the abdominal or flank area with cryolipolysis, shockwave therapy and injection lipolysis (n = 10) or cryolipolysis and shockwave therapy (n = 4). All treatments were conducted the same day. Evaluations were conducted 3 months after treatment and included histological analysis, standardized photography, blinded-investigator efficacy, and safety ratings, as well as patient ratings of satisfaction and tolerance. Results Compared to baseline, the 3-month follow-up histological analysis revealed a more profound subcutaneous adipose tissue reaction with the triple combination therapy (cryolipolysis, injection lipolysis, radial shock wave) than with the double combination with regard to adipocyte damage and grade of inflammation. Waist circumference was significantly reduced in patients of both groups, but patients in the triple combination group were shown to have a significantly more pronounced reduction in subcutaneous fat. Factors that were shown to influence treatment outcome included baseline BMI and waist circumference. Age and gender had no effect. The abdominal area reacted better to the treatment compared to flanks. No significant side effects or adverse events were reported. The procedure was well-tolerated, and the majority of patients were satisfied with the treatment results. Conclusions Combination of cryolipolysis, radial shockwave, and injection lipolysis is a safe, well-tolerated treatment for reduction in subcutaneous fat.
Gesehen am 16.01.2020